The Concept of Educational Quality Management; Review of Private Islamic Educational Institutions - Sari, Maya Inayati (CV. Zabags Qu Publish, 2024)
This study aims to examine the concept of educational quality management in educational institutions, especially in Islamic education at Batam. The method used is qualitative, with literature studies from reference books, journals, and relevant archive documents. The data were analyzed descriptively-analytically with a critical approach. The results of the study indicate that educational quality management manages all educational resources to produce services that meet or exceed customer needs. The basic strategies needed include problem identification, application of quality philosophy, continuous improvement, and stakeholder involvement. In conclusion, educational quality management in Islamic institutions must be implemented comprehensively and integrated to achieve customer satisfaction and continuous performance improvement. Internal quality control systems play an important role in ensuring that results are in accordance with standards. This study offers quality management strategies that are relevant to the context of Islamic education in Indonesia, as well as a comprehensive management approach that involves all institutional aspects.